2004
DOI: 10.1080/00015550310006770
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Sensitizing Effect of Carvone by the Addition of Non-Allergenic Compounds

Abstract: We have previously reported a reduction of sensitization to carvone in guinea pigs when adding non-allergenic, structurally related compounds simultaneously at induction. This study investigates the criteria needed to obtain a reduction of sensitization in contact allergy. Linalool, a non-sensitizer structurally unrelated to carvone, significantly reduced the sensitizing capacity of carvone in guinea pigs. The effect of different concentrations of inhibitors in mixtures with carvone was investigated. No signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, conflicting results were by several research groups. For instance, carvone, a fragrant ingredient and a well-known sensitizer (mechanism for antigen formation is described) [ 139 ], was found to be inhibited by structural and non-structural analogs in guinea pigs [ 140 , 141 ]. On the other hand, studies on guinea pigs revealed no quenching of cinnamic aldehyde and citral [ 142 ].…”
Section: Eo Therapy: Challenges and Research Gapsmentioning
confidence: 99%
“…However, conflicting results were by several research groups. For instance, carvone, a fragrant ingredient and a well-known sensitizer (mechanism for antigen formation is described) [ 139 ], was found to be inhibited by structural and non-structural analogs in guinea pigs [ 140 , 141 ]. On the other hand, studies on guinea pigs revealed no quenching of cinnamic aldehyde and citral [ 142 ].…”
Section: Eo Therapy: Challenges and Research Gapsmentioning
confidence: 99%